Development of an Anchoring System for Protein Display on the Cell Wall Surface of Lactococcus Lactis Mg1363 - Sankara Varma, Nadimpalli Raw (2006)
Lactococcus is one of the lactic acid bacteria that are widely used in various food and fermentation processes. They have been used for many centuries in food fermentation processes and are considered as GRAS organisms that can safely be used in medical and veterinarian applications. The anchoring of proteins to the cell surface of Lactococcus using recombinant DNA techniques is an exciting and emerging research area that holds great promise for a wide variety of biotechnological applications. Presently available anchoring systems are based on recombinant bacteria displaying proteins or peptides on the cell surface. The objectives of this study are to develop surface display vectors and study the display of recombinant proteins on the surface of Lactococcus lactis. Several anchor proteins have been identified in L. lactis. In this study the gene coding for the cell wall binding domain of L. lactis cell wall anchor proteins AcmA and NisP were amplified by PCR and cloned into an E. coli expression vector. Sequencing results showed 98% homology to published sequences. The plasmids designated as pSVacrn and pSVnp were then transformed into E. coli where SDS-PAGE and Western blot analyses showed that the cell wall binding domain of acmA and nisP genes were successfblly expressed at the expected sizes 15 kDa and 18 kDa respectively. After mixing of the purified recombinant AcrnA and NisP proteins with L. Iactis cells, their presence on the bacteria cell surface was observed by whole cell ELISA, ~ i ~ ~ b i n d i n g and fluorescence microscopy analysis. The stability assay indicates that the binding of AcrnA protein to the lactococcal cell surface was stable and can be retained on the cell wall surface for at least 5 days. The results form the pH study indicatedthat low pH had no significant effect on the stability of bound His-tag AcmA protein. Whilst the cell wall binding domain of AcmA was shown to be able to anchor to the cell surface of other Gram-positive bacteria tested in this study, AcrnA protein was not able to bind to the surface of E. coli (Gram-negative) cells. Studies were also carried out to enhance the binding of AcmA protein to L. lactis cells where pretreatment of L. lactis with 10% TCA was shown to improve binding of the AcmA protein. The new method developed for cell surface display of recombinant proteins on L. lactis was evaluated for expression and display of foreign proteins. The gene coding for the N-terminal epitope regions (VP11-67aaa nd VP13s-looaao) f VPl protein of Enterovirus 71 (EV71) were subcloned upstream to the cell wall binding domains sequences of plasmids pSVacm and pSVnp. SDS-PAGE and Western blot results confirmed the expression of N-terminal regions of VP1 protein as AcmA and NisP fusion proteins in E. coli. Wholecell ELISA and imrnunofluorescence microscopy assays showed the successfbl display of VPl protein of EV7 1 on the surface of L. lactis. The success of docking VP 1 1-67aa and VP 1 35-100aa epitopes of VP 1 on the surface of L. lactis cells using --- - the anchoring system developed in this study, open up the possibilities of peptide and protein display for not only Lactococcus but of other Gram-positive bacteria. Preliminary studies showed that mice immunized with L. Iactis displaying VP1147, or VP13s-looafau sion proteins were able to induce an immune response against the VP11- 6 7 o~r V P135-100a(aa ntigens). The new method developed for surface display has the potential to a variety of applications including screening of polypeptide libraries, development of live vaccines, construction of whole cell allosteric biosensors, and signal bansduction studies.